HUBUNGAN SLEEP HYGIENE DAN KUALITAS TIDUR PADA PENDERITA DIABETES MELITUS DI KELURAHAN BABAKAN SARI - Utami, Gina Utami; Juniarti, Neti; Sari, Citra Windani Mambang (STIKES Suaka Insan, 2025)
Sleep disturbances are a common comorbidity among individuals with diabetes mellitus and can negatively impact blood glucose regulation and overall quality of life. This study aims to examine the relationship between sleep hygiene and sleep quality among patients with diabetes mellitus in Kelurahan Babakan Sari. A correlational quantitative design with a cross-sectional approach was applied. A total of 75 respondents were selected using purposive sampling. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) and Sleep Hygiene Index (SHI) instruments. The findings revealed that most respondents had a moderate level of sleep hygiene (50.7%) and poor sleep quality (92%). Pearson correlation analysis indicated a significant positive relationship between sleep hygiene and sleep quality (r = 0.620, p < 0.001). These results suggest that sleep hygiene plays a vital role in determining sleep quality among individuals with diabetes. Therefore, educational interventions promoting healthy sleep habits should be integrated into community-based diabetes management programs.